First report of cowpea mild mottle virus naturally infecting Euphorbia heterophylla in Brazil and worldwide - Rodrigues Silveira, Bárbara R. [UNESP]; Moreira, Ana Clara R. V. [UNESP]; Aguilar Sanchez, Guido; Ribeiro-Junior, Marcos Roberto; Krause-Sakate, Renate (Scientific Societies, 2025)
During the 2023/2024 soybean season in Brazil, producers and extension agents reported increased whitefly (Bemisia tabaci) infestations, especially in São Paulo State, prompting intensified surveillance for cowpea mild mottle virus (CPMMV, Carlavirus vignae), a whitefly-transmitted carlavirus infecting soybean, common bean, and various weeds (Barreto da Silva et al. 2024; Kitajima 2020; Lamas et al. 2017). Field sampling included soybean leaves (hundred samples) and nearby weeds (six samples each species): Euphorbia heterophylla, Macroptilium sp., Commelina benghalensis, Portulaca oleracea, Raphanus raphanistrum, Senna occidentalis, Ipomoea purpurea, Ricinus communis, Digitaria insularis, Amaranthus hybridus, and Richardia brasiliensis. Ten adult whiteflies from soybean were PCR-identified as MEAM-1 using Bem23 primers (De Barro et al. 2003). Total RNA was extracted (Bertheau & Frechon, 1998) from the plant samples and tested by RT-PCR with CPMMV CP primers (Barreto da Silva et al. 2024). CPMMV was detected in soybean (100/100), Macroptilium sp. (6/6), and E. heterophylla (5/6). Symptoms, including foliar mottling and deformation, were observed in soybean and Macroptilium, whereas E. heterophylla was asymptomatic. To confirm the identity of the CPMMV collected from E. heterophylla, the RT-PCR product was Sanger sequenced bidirectionally and analyzed using Geneious Prime 2024.0 software. The CPMMV isolate from E. heterophylla (GenBank acc. no. PQ825744) exhibited 97.7% nucleotide identity with a Brazilian reference isolate (acc. no. MK202583). Genetic divergence was assessed by amplifying the RdRp (1,076 bp; CPMMV-RdRp-F/R) and CP (1,106 bp; CPMMV-CP-F/R) genes from both CPMMV-Eh (E. heterophylla) and CPMMV-soybean. Amplicons were sequenced and analyzed via BLASTn. CPMMV-Eh (PX132324) shared the highest identity at 96.3% in RdRp with acc. no. PV460962 from Passiflora sp. (Brasília), whereas CPMMV-soybean (PX132325) showed the highest identity at 98.5% with acc. no. MV657117 (Goiás). Pairwise RdRp identity between CPMMV-Eh and CPMMV-soybean was 80.8%. In the CP region, CPMMV-Eh (PQ834428) exhibited the highest identity (98.0%) with acc. no. KF554101 (Goiás), while CPMMV-soybean (PQ834429) showed the highest identity (94.3%) with acc. no. OP611426 (Buritama, SP). The pairwise CP identity between CPMMV-Eh and CPMMV-soybean was 84.3%. These findings highlight genetic divergence between CPMMV-Eh and CPMMV-soybean. Sap transmission assays were conducted to evaluate the infectivity of CPMMV-Eh using phosphate-buffered saline (0.5 M, pH 7.2) and carborundum (600 mesh) on five soybean and five E. heterophylla plants. Plants were kept insect-free for 30 days after infection. No symptoms were observed in E. heterophylla, whereas soybean developed yellow mosaic. RT-PCR confirmed CPMMV-Eh infection in both hosts. This constitutes the first documented natural infection of E. heterophylla by CPMMV globally. Given E. heterophylla’s established resistance to glyphosate, acetolactate synthase (ALS) inhibitors, and protoporphyrinogen oxidase (PPO) inhibitors (Adegas et al. 2020; Vargas et al. 2016), its role as a persistent viral reservoir is of agronomic concern. Integration of E. heterophylla into virus surveillance and weed management protocols, particularly along field margins and during fallow periods, is imperative to mitigate inoculum pressure and curtail whitefly-mediated transmission to soybean crops.